2015
DOI: 10.18632/oncotarget.5513
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of the Tcf/beta-catenin complex increases apoptosis and impairs adrenocortical tumor cell proliferation and adrenal steroidogenesis

Abstract: BackgroundTo date, there is no effective therapy for patients with advanced/metastatic adrenocortical cancer (ACC). The activation of the Wnt/beta-catenin signaling is frequent in ACC and this pathway is a promising therapeutic target.AimTo investigate the effects of the inhibition of the Wnt/beta-catenin in ACC cells.MethodsAdrenal (NCI-H295 and Y1) and non-adrenal (HeLa) cell lines were treated with PNU-74654 (5–200 μM) for 24–96 h to assess cell viability (MTS-based assay), apoptosis (Annexin V), expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 46 publications
7
67
0
1
Order By: Relevance
“…Thus, this cell line is a good model to be used to evaluate the effect of the pharmacological modulation of the Wnt/beta-catenin pathway in vitro . Interestingly, we found that inhibition of the Wnt/beta-catenin pathway decreased YAP1 protein expression in parallel to the reduction of beta-catenin expression [21]. Thus, our data support that YAP1 is a Wnt/beta-catenin target in adrenocortical cells.…”
Section: Discussionsupporting
confidence: 74%
“…Thus, this cell line is a good model to be used to evaluate the effect of the pharmacological modulation of the Wnt/beta-catenin pathway in vitro . Interestingly, we found that inhibition of the Wnt/beta-catenin pathway decreased YAP1 protein expression in parallel to the reduction of beta-catenin expression [21]. Thus, our data support that YAP1 is a Wnt/beta-catenin target in adrenocortical cells.…”
Section: Discussionsupporting
confidence: 74%
“…Interestingly, NCI-H295 lacks TP53 p.R337H, but presents other mutations affecting p53 functions (Sampaoli et al 2012, Leal et al 2015, which also could be related to reduced effectiveness of therapies, such as anti-IGF1R.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenic p.S45P mutation of CTNNB1 gene, which results in abnormal beta-catenin nuclear accumulation [20,21], is characteristic of NCI-H295R cells. The effect of AA on beta-catenin sub-cellular localization was investigated.…”
Section: Aa Affects Beta-catenin Translocation Into the Nucleus In Ncmentioning
confidence: 99%